2015
DOI: 10.1016/j.taap.2015.01.005
|View full text |Cite
|
Sign up to set email alerts
|

MAPK pathway activation by chronic lead-exposure increases vascular reactivity through oxidative stress/cyclooxygenase-2-dependent pathways

Abstract: Chronic exposure to low lead concentration produces hypertension; however, the underlying mechanisms remain unclear. We analyzed the role of oxidative stress, cyclooxygenase-2-dependent pathways and MAPK in the vascular alterations induced by chronic lead exposure. Aortas from lead-treated Wistar rats (1st dose: 10 μg/100g; subsequent doses: 0.125μg/100g, intramuscular, 30days) and cultured aortic vascular smooth muscle cells (VSMCs) from Sprague Dawley rats stimulated with lead (20μg/dL) were used. Lead blood… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
27
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 51 publications
3
27
1
Order By: Relevance
“…We recently demonstrated that chronic lead acetate administration in rats, leading to blood concentrations as low as 10-20 lg/dL, elevates BP and increases vascular reactivity [7][8][9]. These results reinforce the idea of hazardous lead effects even at low levels.…”
Section: Introductionsupporting
confidence: 57%
See 1 more Smart Citation
“…We recently demonstrated that chronic lead acetate administration in rats, leading to blood concentrations as low as 10-20 lg/dL, elevates BP and increases vascular reactivity [7][8][9]. These results reinforce the idea of hazardous lead effects even at low levels.…”
Section: Introductionsupporting
confidence: 57%
“…Of the probable mechanisms involved in the genesis and maintenance of BP elevations induced by lead exposure, numerous studies point to increased peripheral vascular resistance due to endothelial [9,10,29] and vascular smooth muscle dysfunction [9], increased endothelin [11], oxidative stress [9,10,12,29] and reduced NO bioavailability [12,29]. Moreover, activation of the renin-angiotensin system, which is closely associated with ANS activation, would also be present in acute and chronic lead toxicities [13,39].…”
Section: Discussionmentioning
confidence: 99%
“…; Simões et al . ). As a result, nNOS and other antioxidant (induced nitric oxide synthase and Cyclooxygenase) systems are depleted leading to an increase in inflammation through oxidative stress (Zhang et al .…”
Section: Discussionmentioning
confidence: 97%
“…MAPK/ErK increases JNK and cJUN which promotes nuclear activation and post-translational modifications of HMGB1 (Chen et al 2012a,b;Dange et al 2015). In addition, previous studies have shown that an increase in MAPK/ErK is associated with up-regulated NADPH oxidase and oxidative stress (Morales et al 2014;Simões et al 2015). As a result, nNOS and other antioxidant (induced nitric oxide synthase and Cyclooxygenase) systems are depleted leading to an increase in inflammation through oxidative stress (Zhang et al 1998;DiCarlo et al 2002;Dai et al 2014).…”
Section: Igf-1r Signaling In Ang Ii-induced Pvn Inflammationmentioning
confidence: 99%
“…Proteins from homogenized arteries were quantified as previously described [22]. Were used mouse monoclonal antibodies anti-COX-2 (1:200; Cayman Chemical, MI, USA) or anti-NADPH subunit NOX1 (gp 22phox , 1:1000; Transduction Laboratories, Lexington, UK), and anti-mouse immunoglobulin antibody conjugated to horseradish peroxidase (1:5000; StressGen, Victoria, Canada).…”
Section: Western Blot Analysismentioning
confidence: 99%